Risk Factors Affecting Pulmonary Disorders of Workers In Indonesia: Literature Review 2017-2022 - Dessy Widiyaristi; Elvi Sunarsih; Rostika Flora; Yuanita Windusari; Mohammad Zulkarnain; Suheryanto Suheryanto (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Pulmonary disorders in 2018 entered the 5th rank as a disease that causes death. Dust and gas are air pollutants that have a high level of toxicity in the environment when entering and accumulating in human respiratory organs for a long time can cause lung function disorders. The purpose of this study was to determine the factors for impaired function in workers in Indonesia. This study used the literature review method with Google Scholar, PubMed, and BioMed Central databases. Search for articles according to topics published from 2017 to 2022 with a working population and research locations in Indonesia. The results of the study obtained a total of 4648 articles, after screening 30 articles were obtained for analysis. From the research it was found that dust exposure and gas exposure were the types of pollutants that caused lung function disorders. The factors that can be modified are setting the length of exposure so that it can affect the working period per year, nutritional status, exercise, smoking habits and the use of Personal Protective Equipment (PPE). Age and gender variables are risk factors that cannot be modified. The longer a person works, the greater the potential hazards that accumulate into the body, especially workers who are in a dusty environment. Therefore, efforts are needed to manage exposure to air pollution in the work environment and routinely conduct medical check-ups for workers, exercise regularly, use PPE, eliminate smoking habits to minimize the occurrence of lung function disorders.